ANALISIS KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN - Muliyadi Jaya (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The main factor differentiating the service companies to others is the service quality. The customers become smarter in their orders and have more demand for the higher standard of the service. Thus, efficiency of the output is greatly needed in order to be able to fulfil the customers’ order. The efficiency of the output means that the employees can produce the output fitting to standard of the time given by the company. Whether the output is effective or not depends on each of the individual characteristics. It is because one of the factors influencing the output of employee is the employee characteristic (personal characteristic). The purpose of this study is examine the role of the individual characteristic variable in the improvement of output of the company found in PT. TIKI JNE Palangka Raya Branch.This study used the quantitative method with an explanation approach. The technique applied in getting the sample is by using a simple random sampling. One of techniques to collect the data is by using Questionnaire, which is distributed to thirty-four employees of PT. TIKI JNE Palangka Raya Branch. The instruments existed in the questionnaire are firstly tested by Cronbach Alpha. The data analysis use descriptive and quantitative method. The descriptive method uses crosstab (cross tabulation) by analyzing every variable crossly. While the quantitative method applied the discriminated stepwise model because the dependent variable is the categorical one and canonical correlation analysis. The results show that there are four independent variables having the significant role in the improvement of employee’s output in PT. TIKI JNE Palangka Raya Branch, such as the variable of the personality (0,548), behavioral (0,433), and ability (-0,315). Therefore, it can be concluded that to be able to achieve of the expected output, it is important to notice personality, behavioral as required in a certain position and to adapt between the personality of the employee and the position occupied.Keywords : Output, Individual Characteristic